Appraisal of officers - Jaworski, Bogdan (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The appraisal of an officer takes place through a service review. It takes place periodically or in specifically indicated situations. The official opinion is one of the motivators for better performance and for shaping the attitudes necessary in a given service. In the article, the focus was placed on the analysis of the legislation and on the course of the proceedings in business reviews in selected representative uniformed services. The research material has been supplemented with numerous judgments of administrative courts in cases regarding the appraisals of officers. Also, the views of the doctrine connected theoretically with the ongoing processes of opinion-making were presented. The collected research material and the analysis of the legal provisions allowed formulation of conclusions which may be used in the law-making processes in terms of professional pragmatics in the issues concerning official opinions of officers.